REIMAGINING SWEARING EFFECTS ONLINE: THE USE OF SWEARWORDS IN NEWS AUDIENCE COMMENTING - Kwon, K. Hazel; Cho, Daegon (AoIR Selected Papers of Internet Research, 2015)
The aim of this study is to explore swearing effects on online public perceptions of other audiences’ comments, with a focus on swearing effects in interplay with anonymity and topical difference (political vs. non-political) on the volume of public attention (total votes received by a comment) and perceptional valence (a difference between positive and negative votes).